Tindak Pidana Penipuan Dalam Perspektif Hukum Positif dan Fiqih Jinayah: Studi Putusan Pengadilan Negeri Bukittinggi - Selly Stephani; Syaiful Munandar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Islam prohibits all types of crimes, including all forms of fraud. Fraud is an evil act committed by someone by deceives others. When viewed from the perspective of the actions and elements of fraud, it appears that there are similarities between fraud and crimes regulated in Islamic law, such as ghulul, treason, and lying. The research approach used is Normative Juridical legal research. The purpose of this study is to determine the regulation of the Criminal Act of Fraud in the Criminal Code and Fiqh Jinayah. And how is the process of resolving the Criminal Act of Fraud in case NO 6 / Pid.B / 2024 / PN Bkt, with the following conclusions: In Islamic criminal law, perpetrators of fraud will receive ta'zir punishment. This is because ta'zir is a type of punishment whose final decision is in the hands of the government, especially the judge who gives the verdict. The judge has the freedom to choose the type of punishment based on their assessment. This also applies to cases of fraud that have been regulated in Article 378 of the Criminal Code.